A Personal Desktop Liquid-Metal Printer as a Pervasive Electronics Manufacturing Tool for Society in the Near Future. (December 2015) - Yang, Jun; Yang, Yang; He, Zhizhu; Chen, Bowei; Liu, Jing
ABSTRACT: It has long been a dream in the electronics industry to be able to write out electronics directly, as simply as printing a picture onto paper with an office printer. The first-ever prototype of a liquid-metal printer has been invented and demonstrated by our lab, bringing this goal a key step closer. As part of a continuous endeavor, this work is dedicated to significantly extending such technology to the consumer level by making a very practical desktop liquid-metal printer for society in the near future. Through the industrial design and technical optimization of a series of key technical issues such as working reliability, printing resolution, automatic control, human-machine interface design, software, hardware, and integration between software and hardware, a high-quality personal desktop liquid-metal printer that is ready for mass production in industry was fabricated. Its basic features and important technical mechanisms are explained in this paper, along with demonstrations of several possible consumer end-uses for making functional devices such as light-emitting diode (LED) displays. This liquid-metal printer is an automatic, easy-to-use, and low-cost personal electronics manufacturing tool with many possible applications. This paper discusses important roles that the new machine may play for a group of emerging needs. The prospective future of this cutting-edge technology is outlined, along with a comparative interpretation of several historical printing methods. This desktop liquid-metal printer is expected to become a basic electronics manufacturing tool for a wide variety of emerging practices in the academic realm, in industry, and in education as well as for individual end-users in the near future.